Phase Open Fault Tolerant Control of High Reliability Doubly-Salient Wound-Field Machine - Liwei Shi; Bo Zhou (Universitas Ahmad Dahlan, 2014)
Doubly Salient Wound-Field Machine (DSWFM) can be employed on aeronautics starter-generator because it has good performance on both power generation and starting. To improve the system reliability, a three-phase four bridge legs converter which has fault tolerant capability is proposed to solve one phase open-circuit fault problem of the DSWFM. And the advantage of the proposed converter to the full-bridge converter fault-tolerant mode is analyzed. With the study of DSWFM theory and torque equation, a constant torque fault-tolerant strategy is proposed to keep the performance and reduce the torque ripple. The drive system after fault identification can be reconstructed by the proposed method, and the machine performance can recover quickly. Simulations confirm the feasibility of the proposed fault tolerant system.